Polycyclic aromatic hydrocarbons and cytochrome P450 in HIV pathogenesis - Rao, P. S. S.; Kumar, Santosh (Frontiers in Microbiology, 2015)
High prevalence of cigarette smoking in HIV patients is associated with increased HIV pathogenesis and disease progression. While the effect of smoking on the occurrence of lung cancer has been studied extensively, the association between smoking and HIV pathogenesis is poorly studied. We have recently shown the possible role of cytochrome P450 (CYP) in smoking/nicotine-mediated viral replication. In this review, we focus on the potential role of CYP pathway in polycyclic aromatic hydrocarbons (PAH), important constituents of cigarette smoke, mediated HIV pathogenesis. More specifically, we will discuss the role of CYP1A1 and CYP1B1, which are the major PAH-activating CYP enzymes. Our results have shown that these CYPs are highly induced by cigarette smoke condensate (CSC) in HIV-infected macrophages, which perhaps increase HIV replication. CSC contains PAH, which are known to be activated by CYP1A1 and CYP1B1 into procarcinogens/toxic metabolites. The expression of these CYPs is regulated by aryl hydrocarbon receptors (AHR), the cellular target of PAH, and an important player in various diseases including cancer. We propose that PAH/AHR-mediated CYP pathway is a novel target to develop new interventions for HIV positive smokers.